ANALISIS RESPON KONSUMEN PADA KUALITAS PRODUK KULINER (Kasus Restoran Ayam Penyet Pak Ulis Cabang Pekanbaru) - Rahman Dani; Sri Zuliarni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Consumer response is a state that is easily swayed to give a response to stimuli from theenvironment that can guide a person's behavior to take a decision. Response usually plays amajor role in shaping behavior. In many ways a response to a particular brand often influencethe consumer to make a purchase or not. Home or a restaurant meal is a type of food servicebusiness which is housed in a permanent building some or all of which sell and serve food andbeverages to the public. In general, foods consumed with the aim to meet the most basicrequirements, namely the primary human needs. Along with the times and the level of thedeveloping economy of the community have an impact on the tendency of individuals or group ofpeople to eat outside the home has increased the practical and economic reasons. In thesecircumstances the consumer in a position of strength, a lot of options for a requirement thatconsumers are confused to choose a product. In the face of stiff competition and established apowerful brand can give credibility to a new product that is also a clear differentiator, valuedand continuous. The quality of the product is believed to have a tremendous power to captivatepeople to buy a product or service that is representative, the purchase decision is more oftenbased on a consideration of the quality of the product.In meeting the needs of the consumer pack chicken restaurant penyet ulis Pekanbarubranch already doing things right and necessary in its execution, yet the problem still can not beavoided. Responding to the chicken restaurant penyet pack ulis Pekanbaru branch as theprovider of culinary products using appropriate policies in resolving the problem by taking intoaccount the performance, features, service ability, aesthetics, and perceived quality dimensionsare included in the product.Keywords: consumer response, quality, culinary product.